Prebiotics as ingredients in future beverage product innovation. - Yusof, Salmah; Abdul Manap, Mohd Yazid; Wong, Peng Kong; Yousaf, Mohamad Sohail (2001)
Today's consumers are more selective and meticulous, demanding foods that would not only fulfill basic nutrition. but of good taste and healthy. Since beverage represents a substantial portion of consumers' food intake, it is vital for manufacturers to respond to the changing need of consumers. The current trend is to look at long-term effect of food intake towards health. Prebiotics are reported to provide this beneficial effect. This paper will define the term prebiotics and explain their chemical characteristics and functions in human health. It will also highlight the promising benefits of using prebiotcs in new beverage product innovations and compare their performance with ordinary electrolytic drinks.